The Effect Of Problem-Based Learning Instruction Activities on Problem Solving skills and Mathematical Connection skills of third year Students - PHOMMANITH , Khamsone; KEOPHASITH, Vatsana; BOUSITH, Oudom; DOUNGCHAN , Boy; SAYDUANGTA, Soulinthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The purposes of this research were to compare mathematical problem solving Skills and mathematical connection skills for third year students before and after providing problem-based learning instruction activities. The target groups of this study were 19 third year students who are studying mathematics in the first semester, academic year 2019-2020 at Faculty of Education. The participants were selected by using cluster random sampling technique. The instruments included lesson plan, achievement test, attitude test, and focus group. The experiment lasted for 16 periods. The One-Group pretest-posttest design was used for this study. The data were analyzed by using t-test for dependent samples, mean, and standard deviation The findings were as follows: The mathematical problem solving skills for third year students after being taught by using problem-based learning instruction activities were higher than that before being taught at 0.01 level of significance. The mathematical connection skills for third year students after being taught by using problem-based learning instruction activities were higher than that before being taught at 0.01 level of significance and they got high level scores in attitude towards mathematics.